1999
DOI: 10.1159/000018279
|View full text |Cite
|
Sign up to set email alerts
|

Retinol and Retinyl Ester Epidermal Pools Are Not Identically Sensitive to UVB Irradiation and Anti-Oxidant Protective Effect

Abstract: Background: UV irradiation can deplete epidermal vitamin A, thus the hypothesis that UV-induced depletion of vitamin A in sun-exposed skin is involved in the pathogenesis of skin cancers and skin ageing. Objectives: In this study we addressed two questions: (1) Are retinol (ROL) and retinyl esters (RE) – the two predominant forms of vitamin A – equally sensitive to the action of UVB, and (2) could the depletion be prevented by anti-oxidants? Methods: Hairless mice were irradiated with a single UVB dose, corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(89 citation statements)
references
References 25 publications
3
85
1
Order By: Relevance
“…One investigation of UV light exposure on hairless mice found that it greatly reduced the concentrations of retinyl esters, although all-trans-retinol was largely unaffected. This suggested that retinoid-binding proteins such as CRBP I protect all-trans-retinol from the damaging effects of UV light (64,65). Although more recent work has suggested that CRBP's primary role in UV-mediated damage is more related to retinoid mobilization in response to the light-induced injury (66), other studies of UV exposure to human skin and to Gecko lens further support the protective role of CREB I (64,67).…”
Section: Protective Effect Of Cralbp On the Reverse Isomerization-mentioning
confidence: 99%
“…One investigation of UV light exposure on hairless mice found that it greatly reduced the concentrations of retinyl esters, although all-trans-retinol was largely unaffected. This suggested that retinoid-binding proteins such as CRBP I protect all-trans-retinol from the damaging effects of UV light (64,65). Although more recent work has suggested that CRBP's primary role in UV-mediated damage is more related to retinoid mobilization in response to the light-induced injury (66), other studies of UV exposure to human skin and to Gecko lens further support the protective role of CREB I (64,67).…”
Section: Protective Effect Of Cralbp On the Reverse Isomerization-mentioning
confidence: 99%
“…The whole processing of α-tocopherol extraction was performed at a cool temperature (4°C) as described previously for the retinoid assay [13]. Epidermis was minced with scissors in 1.92 ml extraction buffer, then epidermis or collected squames were homogenised by using a Polytron PT 3100 homogeniser in 1.92 ml extraction buffer.…”
Section: Methodsmentioning
confidence: 99%
“…The homogenate was sonicated for 10 s at a low power (50 W) and centrifuged for 10 min at 12,000 g , then the supernatant was extracted with 4 ml hexane. The hexane fraction was evaporated to dryness under nitrogen flux, then the sample was reconstituted in 100 µl methanol, before being injected into the HPLC [13]. α-Tocopherol was detected by fluorescence (excitation: 292 nm; emission: 330 nm), and retinyl acetate (internal standard) was detected by UV absorption at 325 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Retinoids were applied at 10 µM for 4, 24 or 96 hours in BDVII keratinocytes or B16 melanocytes, then the cells were lysed and harvested by sonication in 50 mM acetate buffer pH 4, and intracellular retinoids were analysed by high performance liquid chromatography (HPLC) and UV detection as described ( Table 1) [17]. Results shown in Figs. (2-5) are expressed as (pmol retinoid/mg protein) and represent the means of duplicate experiments performed in the same series of culture.…”
Section: Retinoid Analysismentioning
confidence: 99%